Bodipy Derivatives as Triplet Photosensitizers and the Related Intersystem Crossing Mechanisms - Chen, Kepeng; Dong, Yu; Zhao, Xiaoyu; Imran, Muhammad; Tang, Geliang; Zhao, Jianzhang; Liu, Qingyun (Frontiers in Chemistry, 2019)
Recently varies of Bodipy derivatives showing intersystem crossing (ISC) have been reported as triplet photosensitizers, and the application of these compounds in photocatalysis, photodynamic therapy (PDT), and photon upconversion are promising. In this review we summarized the recent development in the area of Bodipy-derived triplet photosensitizers and discussed the molecular structural factors that enhancing the ISC ability. The compounds are introduced based on their ISC mechanisms, which include heavy atom effect, exciton coupling, charge recombination (CR) induced ISC, using a spin converter and radical enhanced ISC. Some transition metal complexes containing Bodipy chromophore are also discussed. The application of these new triplet photosensitizers in photodynamic therapy, photocatalysis, photon upconversion are briefly commented. We believe the study of new triplet photosensitizers and the application of these novel materials in the above mentioned areas will be blooming.